Linear periodic boundary-value problem for a second-order hyperbolic equation. I - Khoma, N. H. (Ukrains’kyi Matematychnyi Zhurnal, 1998)
In three spaces, we obtain exact classical solutions of the boundary-value periodic problem u tt−a 2 u xx=g(x,t), u(0,t)=u(π,t)=0, u(x,t+T)=u(x,t)=0, x,t∈ĝ